CULTURAL AND HUMANITARIAN RELATIONS BETWEEN UZBEKISTAN AND THE PHILIPPINES: HISTORY AND THE CONTEMPORARY STAGE - Шакиров И. Р. (TARIXIY TADQIQOTLAR, 2026)
The present article provides an analysis of the bilateral cooperation between Uzbekistan and the Philippines in the cultural and humanitarian sphere. Based on the examination of archival materials, it is determined that in the 1990s, despite the establishment of diplomatic relations, the dynamics of the development of bilateral cultural and humanitarian relations between Uzbekistan and the Philippines displayed a negative trend. The article substantiates that the primary factor behind the negative dynamics of bilateral relations in the 1990s was the absence of cultural and historical affinity between the two states. At the same time, drawing on an analysis of official documents, the article demonstrates that since 2017 a positive trend in the development of cultural and humanitarian relations between Uzbekistan and the Philippines has been observed.